Efficiency and safety of leflunomide in rheumatoid arthritis: Results of a Russian observational multicenter of trial - R. M. Balabanova (Современная ревматология, 2015)
Methotrexate or leflunomide is used as a first-line synthetic disease-modifying anti-rheumatic drug in the therapy of rheumatoid arthritis (RA). In 2011, the Russian Federation registered and since it has been successfully using leflunomide**.Objective: to evaluate the efficacy and tolerability of leflunomide** used to treat RA in routine clinical practice.Subjects and methods.The investigation enrolled patients with varying duration of RA that met the 1987 classification criteria. The patients were followed up in 33 healthcare facilities of Russia from March 2013 to October 2014. A total of 235 patients were randomized; the data of 196 patients were statistically processed. The mean age of the patients was 52.4±11.8 years; the mean duration of the disease was 75.4±69.1 months. The disease activity estimated by DAS28 and CDAI were 5.5±1.2 and 35.1±14.3 scores, respectively. 105 and 57 patients had X-ray Stages II and III disease, respectively. 80.1% of the patients were positive for rheumatoid factor and anti-cyclic citrullinated peptide antibodies. According to the instruction of its use, leflunomide was administered in a dose of 100 mg/day during the first 3 days and then in that of 20 mg/day. When adverse reactions (ARs) occurred, it was recommended that the daily dose of the drug was decreased to 10 mg. The patients were examined before and 1, 3, and 6 months after treatment. The investigators measured the number of tender joints (NTJ) and that of swollen joints (NSJ), and visual analog scale (VAS) pain intensity, performed a laboratory examination involving clinical blood test, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP), in patients during their visits to physicians. The disease activity was assessed with DAS28 and CDAI and ARs were recorded.Results. Six-month therapy reduced the mean NSJ from 10.9 to 7.5%, NTJ from 12.3 to 8.9, VAS pain intensity from 64.1 to 39.3 mm, on average, ESR from 37.04 to 23.6 mm/hr, and CRP from 27.8 to 12.35 mg/l. By 6 months of therapy, low and moderate RA activities estimated by DAS28 were noted in 70.9% of cases and those by CDAI in 61.2%. No serious ARs were detected during the study.Conclusion. The findings suggest that leflunomide shows a good clinical efficacy and tolerability.